Why might high-intensity interval training be attractive to the recreationally inactive contingent? - Moment A.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to objectify the dynamics of affective valence in a group of healthy recreationally inactive females in response to low-volume, high-intensity interval training with their own body weight (whole-body HIIT). Methods and structure of the study. Recreational-inactive healthy female students (n=11) who met the inclusion criteria took part in the experiment. Affective valence, heart rate and external parameters of physical activity were recorded. Results and conclusions. Affective valence significantly decreased from 3.0 (3.0–3.0) to 0.0 (-1.0–1.0) points after overcoming the 85% threshold of the maximum predicted heart rate value, but after a cool-down (3.0 (3.0–5.0) points) the majority of subjects (54.5%) felt better than before the training (3.0 (2.0–3.0) points), which confirms presence of affective rebound. Thus, it is fair to conclude that the state of affective elation experienced after training may be one of the factors of adherence to low-volume whole-body HIIT.